ANALISIS SISTEM PENDUKUNG KEPUTUSAN DALAM MENYELEKSI PROPOSAL PROGRAM KREATIVITAS MAHASISWA PENELITIAN TERBAIK DI AMIK TUNAS BANGSA PEMATANGSIANTAR DENGAN METODE MOORA - Alifah, Winanda; Solikhun, Solikhun; Lubis, Muhammad Ridwan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
The Student Creativity Program is the most awaited activity for every state and private university in Indonesia. In this activity each college tried to send as many research proposals as possible with the aim of winning this PKM activity and the hope to improve the quality of a lecturer and student at the college. This PKM activity is included in a prestigious activity because this activity is organized by the Directorate General of Learning and Student Affairs. Therefore AMIK Tunas Bangsa as a private university also wants to participate in PKM activities, especially in the field of research. In 2017 many Tunas Bangsa AMIK students participated in the research proposal submission. With so many students who want to participate, make the lecturers select first proposals that are considered good or feasible before being uploaded on the PKM page. To facilitate the selection of the proposal, the Decision Support System using the MOORA method (Multi Objective Optimization on the Basic Ratio Analysis) is used in the hope of obtaining proposals that are truly feasible to submit to PKM-P activitiesKeywords: SPK, MOORA, Selection of PKM-Research Proposals The Student Creativity Program is the most awaited activity for every state and private university in Indonesia. In this activity each college tried to send as many research proposals as possible with the aim of winning this PKM activity and the hope to improve the quality of a lecturer and student at the college. This PKM activity is included in a prestigious activity because this activity is organized by the Directorate General of Learning and Student Affairs. Therefore AMIK Tunas Bangsa as a private university also wants to participate in PKM activities, especially in the field of research. In 2017 many Tunas Bangsa AMIK students participated in the research proposal submission. With so many students who want to participate, make the lecturers select first proposals that are considered good or feasible before being uploaded on the PKM page. To facilitate the selection of the proposal, the Decision Support System using the MOORA method (Multi Objective Optimization on the Basic Ratio Analysis) is used in the hope of obtaining proposals that are truly feasible to submit to PKM-P activities.Keywords:SPK, MOORA, Selection of PKM-Research Proposals